1987
DOI: 10.1002/1097-0142(19870815)60:4<772::aid-cncr2820600411>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac disease after mediastinal irradiation for seminoma

Abstract: One hundred twenty-four patients with seminoma (119 primary testis, five primary extragonadal) were treated between 1968 and 1984 at the Joint Center for Radiation Therapy. Fifty-seven of the 124 patients were treated with irradiation to the mediastinum as well as to an infradiaphragmatic field. One patient received supradiaphragmatic radiotherapy only. The remaining patients had radiation treatment limited to the infradiaphragmatic field only. Median dose to the mediastinum among the 58 patients was 2400 cGy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Whereas mediastinal irradiation has been associated with increased CVD risk in TC patients [11][12][13][14], there are conflicting data regarding the association between infradiaphragmatic irradiation and CVD risk. Zagars et al [12] reported a 1.8-fold increased risk for cardiac death in seminoma patients treated with infradiaphragmatic radiotherapy alone with follow-up beyond 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas mediastinal irradiation has been associated with increased CVD risk in TC patients [11][12][13][14], there are conflicting data regarding the association between infradiaphragmatic irradiation and CVD risk. Zagars et al [12] reported a 1.8-fold increased risk for cardiac death in seminoma patients treated with infradiaphragmatic radiotherapy alone with follow-up beyond 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between cisplatin-based therapy and an unfavorable cardiovascular (CV) risk profile and CV morbidity [3][4][5][6][7][8][9][10][11]. Moreover, radiotherapy has also been associated with CV morbidity and mortality [10][11][12][13][14][15]. The interval between TC treatment and the occurrence of the first therapy-related cardiovascular disease (CVD) event appears to be decades rather than years [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, heart disease associated with MRT is a significant cause of late morbidity and mortality [2,6,11,13,15]. In Hodgkin's disease, heart disease is the second-most common cause of late death [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic treatment to these sites was abandoned in the 1980s after reports demonstrated elimination of prophylactic RT to the mediastinum and SCL regions did not compromise survival but did increase the incidence in RTrelated cardiac disease. [1][2][3][4][5] In 1999, the Medical Research Council reported results evaluating RT to the paraaortic field alone (PAN) versus the traditional "dog-leg" treatment to the PAN and ipsilateral pelvis. Overall survival was not significantly different but local-regional recurrence was increased; patients who relapsed in the pelvis were successfully salvaged with chemotherapy.…”
mentioning
confidence: 99%